(untitled) (Swiss Medical Weekly, 2014)
PRINCIPLES: The incidence of hepatocellular carcinoma is rising. However, this is occurring not only in developing nations, but in industrial countries as well. Surveillance programmes, classification systems and therapeutic options have improved, but there is a lack of data regarding their impact on the prognosis of this difficult-to-treat cancer. MATERIALS AND METHODS: We evaluated 484 patients and reported on disease stage, therapeutic procedures and survival time. Data were compared with a historical cohort treated in the same centre 10 years before. RESULTS: In this cohort, the main reason for liver disease was alcoholism, although hepatitis B remains the leading cause of hepatocellular carcinoma worldwide. Now, most patients have compensated liver function and hepatocellular carcinoma is diagnosed in the early tumour stages (it was diagnosed in the advanced disease stages in the previous cohort). Overall, median survival time was 62.4 weeks, 1-year survival was 58.6% and 3-year survival was 23.2%. Survival time correlated with the stage of liver disease, tumour stage and with therapeutic options. CONCLUSION: Surveillance programmes lead to diagnosis in earlier tumour stages. Differentiated classification systems allow individualised therapeutic approaches. Earlier cancer stage and compensated liver function allow combination or sequential therapy, which was nearly impossible some years ago but is an option for most now. Primary liver cancer remains a difficult-to-treat malignancy, but the prognosis has improved remarkably, at least in the western world.